1971
DOI: 10.1530/jrf.0.0260373
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Cholinesterase Isoenzymes Due to Oral Contraceptives

Abstract: Many changes have been noted in the plasma proteins of women taking oral contraceptives and a similarity between the metabolic effects of oral contraceptive therapy and pregnancy has been observed by Tyler (1964) as well as by Crawford & Rudofsky (1966). The existence of diminished serum cholinesterase activity in pregnancy (Schnider, 1965;Robertson, 1966)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Levels at birth are one-fourth that in adults, but these levels increase rapidly reaching adult levels by the second month of life. In adults, enzyme activity is reported to show large temporal variations over the course a year, is higher in men than in women, and is lower in women taking oral contraceptives and in individuals with liver disease (30-50% in acute and longstanding chronic hepatitis) (Whittaker et al, 1971;Sidell and Kaminskis, 1975;Hayes, 1982;Sidell, 1992;Kisicki, 1999). Decreases of 50-70% occur in advanced cirrhosis and carcinoma with metastasis to the liver (Kisicki, 1999).…”
Section: Iic7 Role Of Cholinesterases In Chlorpyrifos Toxicitymentioning
confidence: 99%
“…Levels at birth are one-fourth that in adults, but these levels increase rapidly reaching adult levels by the second month of life. In adults, enzyme activity is reported to show large temporal variations over the course a year, is higher in men than in women, and is lower in women taking oral contraceptives and in individuals with liver disease (30-50% in acute and longstanding chronic hepatitis) (Whittaker et al, 1971;Sidell and Kaminskis, 1975;Hayes, 1982;Sidell, 1992;Kisicki, 1999). Decreases of 50-70% occur in advanced cirrhosis and carcinoma with metastasis to the liver (Kisicki, 1999).…”
Section: Iic7 Role Of Cholinesterases In Chlorpyrifos Toxicitymentioning
confidence: 99%
“…The first sample was taken before marriage and the second after marriage when taking oral contraceptives. We have previously observed that not only is the cholinester ase activity decreased by oral contracep tives but that the iso-enzyme pattern fol lowing electrophoresis is also changed [Whittaker et al, 1971], Both quickly re turn to normal on cessation of oral contra ceptives. The present observation is, to our knowledge, the first indication that the ex tent of immunobinding protein also de creases with the use of oral contraceptives.…”
Section: Resultsmentioning
confidence: 98%